Insights into CODE-DE – Germany’s Copernicus data and exploitation platform - Tobias Storch; Christoph Reck; Stefanie Holzwarth; Bert Wiegers; Nico Mandery; Ulrich Raape; Christian Strobl; Rouven Volkmann; Martin Böttcher; Andreas Hirner; Johanna Senft; Nicolae Plesia; et al. (Big Earth Data, 2019)
This article presents and analyses the modular architecture and capabilities of CODE-DE (Copernicus Data and Exploitation Platform – Deutschland, www.code-de.org), the integrated German operational environment for accessing and processing Copernicus data and products, as well as the methodology to establish and operate the system. Since March 2017, CODE-DE has been online with access to Sentinel-1 and Sentinel-2 data, to Sentinel-3 data shortly after this time, and since March 2019 with access to Sentinel-5P data. These products are available and accessed by 1,682 registered users as of March 2019. During this period 654,895 products were downloaded and a global catalogue was continuously updated, featuring a data volume of 814 TByte based on a rolling archive concept supported by a reload mechanism from a long-term archive. Since November 2017, the element for big data processing has been operational, where registered users can process and analyse data themselves specifically assisted by methods for value-added product generation. Utilizing 195,467 core and 696,406 memory hours, 982,948 products of different applications were fully automatically generated in the cloud environment and made available as of March 2019. Special features include an improved visualization of available Sentinel-2 products, which are presented within the catalogue client at full 10 m resolution.